2020
DOI: 10.48550/arxiv.2010.02450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutron skin thickness of ${}^{208}$Pb determined from reaction cross section for proton scattering

Shingo Tagami,
Tomotsugu Wakasa,
Jun Matsui
et al.

Abstract: Background: Reaction cross sections σR are available as a function of incident energy Ein for p scattering on a 208 Pb target. Very lately, we reanalyzed interaction cross sections σI (≈ σR)) for 42−51 Ca+ 12 C scattering at Ein = 280 MeV per nucleon, using the chiral (Kyushu) g-matrix folding model with the densities calculated with Gongny-HFB (GHFB) with and without the angular momentum projection (AMP). We determined neutron skin r skin and proton, neutron, matter radii, rp, rn, rm for the σI, using the Kyu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The R P V skin value is considerably larger than the other experimental values which are significantly model dependent [11][12][13][14]. The nonlocal dispersive-optical-model (DOM) analysis of 208 Pb deduces r DOM skin = 0.25 ± 0.05 fm [15], The chiral (Kyushu) g-matrix folding model determines r 208 skin = 0.27 ± 0.03 fm from reaction cross section σ R in 30 ≤ E in ≤ 100 MeV [16]. These values are consistent with R P V skin .…”
Section: Introduction and Conclusionmentioning
confidence: 89%
“…The R P V skin value is considerably larger than the other experimental values which are significantly model dependent [11][12][13][14]. The nonlocal dispersive-optical-model (DOM) analysis of 208 Pb deduces r DOM skin = 0.25 ± 0.05 fm [15], The chiral (Kyushu) g-matrix folding model determines r 208 skin = 0.27 ± 0.03 fm from reaction cross section σ R in 30 ≤ E in ≤ 100 MeV [16]. These values are consistent with R P V skin .…”
Section: Introduction and Conclusionmentioning
confidence: 89%
“…this suggests rather soft slope parameters around 27 MeV, in contrast to the 208 Pb results of PREX II and Refs. 2,3…”
Section: Ca48-sly7˙ws-mpla˙vbp˙orig˙pdftex˙bblmentioning
confidence: 99%
“…A new method that relies more directly on another experimental observable, the reaction cross section σ R , was proposed in Refs. 2,3 From the experimental perspective, this is a method to extract R skin from σ R based on a reaction model with a microscopic optical potential. At the same time, from a theoretical perspective, this improves the calculated R skin given by mean-field models with energy-density functionals whose parameters might not yet be fully constrained.…”
mentioning
confidence: 99%
“…In the previous work [8], we determined the neutron skin r 208 skin = 0.25 fm from the central values of σ R (EXP) of p+ 208 Pb scattering in E in = 40 − 81 MeV, using the chiral (Kyushu) g-matrix folding model with the densities calculated with Gongny-HFB (GHFB) with the angular momentum projection (AMP), The g-matrix folding model is a standard way of obtaining microscopic optical potential for proton scattering and nucleus-nucleus scattering [9][10][11][12][13][14][15][16][17][18]. Applying the folding model with the Melbourne g-matrix [12] for interaction cross sections σ I for Ne isotopes and σ R for Mg isotopes, we found that 31 Ne is a deformed halo nucleus [19], and deduced the matter radii r m for Ne isotopes [20] and for Mg isotopes [21].…”
Section: Introduction and Conclusionmentioning
confidence: 95%